FAD2 and FUT1 Gene Expression in Breastmilk Cells are Associated with Maternal Dietary Intake - Toto Sudargo; Ali Rosidi; Atika Anif Prameswari; Bianda Aulia; Adisti Qamahadlina Larasati; Mutia Ulfah; Shofarina Adilah; Sri Sugiharti; Urip Tri Wijayanti; Sheila Rosmala Putri; Rio Jati Kusuma; Uliana Noor Setiawati Ulvie (Media Gizi Indonesia, 2026)
Background: Breastfeeding provides babies with the best nutrients possible and is essential for promoting their development. Objectives: The purpose of this study was to investigate the connection between the expression of the fatty acid desaturase (FAD) and FUT genes in breast milk cells and the nutritional status, dietary consumption, and growth of the newborn. Methods: In Jombang, East Java, Indonesia, 52 pairs of nursing women and their babies participated in a cross-sectional study. Breast milk samples were collected for mRNA expression analysis using RT-qPCR, while dietary, sociodemographic, anthropometric, and child growth data were assessed using standardized protocols. Results: The majority of mothers had inadequate energy (78.8%) and protein (42.3%) intake, while 76.9% met adequate iron intake. Higher maternal energy (69.5% vs. 59.5%, p<0.001), protein (95.5% vs. 80.3%, p=0.033), and iron intake (136% vs. 105%, p=0.023) were significantly associated with increased FUT1 gene expression. Additionally, higher FAD2 gene expression was linked to increased maternal energy intake (p=0.045) and older maternal age (p=0.004). Interestingly, FUT3 gene expression was elevated in mothers of lower-birth-weight infants (3003 ± 551 g vs. 3302 ± 411 g, p=0.031). Conclusions: These findings emphasize the influence of maternal nutrition on functional gene expression in breastmilk, with potential implications for infant health and development.